Evaluation of acute toxicity of neodymium and yttrium in zebrafish (Danio rerio) embryos - Lora-Benítez, Antonio Jesús; Molina-López, Ana María; Mora-Medina, Rafael; Aguilar-Herrera, Jhon Edgardo; Ayala-Soldado, Nahúm; Moyano-Salvago, Rosario (Frontiers in Environmental Science, 2024)
Rare earth elements are a group of chemicals widely utilized in industry, leading to ecosystem contamination. Due to the lack of regulatory measures, there exists a considerable gap in knowledge concerning their potential to induce adverse effects in organisms. Zebrafish serve as a species utilized in evaluating the risk of potentially toxic substances in the aquatic ecosystem. Our objective was to evaluate the acute toxicity in zebrafish embryos induced by two of the most used rare earth elements, neodymium, categorized as a light element, and yttrium, as a heavy element. We followed OECD guideline nº 236 "Fish Embryo Acute Toxicity Test", exposing embryos to concentrations of 6.4, 16, 40, 100, and 250 mg/L, and calculated the LC50. Our study revealed comparable LC50 values for both elements (55.58 mg/L for Nd, and 45.61 mg/L for Y), suggesting a probable similarity in toxicity. These concentrations values have previously been identified in various contaminated regions globally, presenting a cause for concern.